Réponses

2013-03-02T09:37:04+01:00

((1 + V5)/2)² = (1 + 2V5 + 5)/4 = 2(V5 + 3)/4 = (V5 + 3)/2
(1 + V5)/2 + 1 = (3 + V5)/2


                                                  x² = x + 1
                                       x² - x - 1 = 0
                       (x - 1/2)² - 1/4 - 1 = 0
                             (x - 1/2)² - 5/4 = 0
  (x - 1/2 - V5/2)(x - 1/2 + V5/2) = 0
                      x - 1/2 - V5/2 = 0 ou x - 1/2 + V5/2 = 0
                          x = (1 ++ V5)/2 ou x = (1 - V5)/2